Microseismic monitoring and stability analysis of the left bank slope in Jinping first stage hydropower station in southwestern China - Xu, N.W.; Tang, C.A.; Li, L.C.; Zhou, Z.; Sha, C.; Liang, Z.Z.; Yang, J.Y. (International journal of rock mechanics and mining sciences (Oxford, England : 1997), 2011)
Risks associated with the left bank slope of Jinping first hydropower station in southwestern China are growing as a result of excavation of the dam foundation ditch and various tunnels, as well as grouting to soft strata. To improve our understanding of the slope instability and resolve the complex subsurface conditions of the highly fractured rock mass, a microseismic monitoring system was installed in June 2009, which is the first time such a technique has been introduced into stability analysis of a high steep rock slope in China. The microseismic monitoring system consists of a data acquisition unit, a data processing unit and a three-dimensional array of uniaxial accelerometers. In order to analyze the correlation between seismicity and potential slip surface of the slope, a numerical model was implemented to analyze the failure processes and stability of the slope. The monitoring results illustrate that microseismic events mainly occur as a strip along the spandrel groove of the dam, which coincides with the potential slip surface obtained from numerical analysis, especially at the bottom of the slope. Therefore, the comprehensive method incorporating microseismic monitoring and numerical analysis has been proven to be very promising in instability prediction of rock slope subject to identification and delineation of potential slip surface and failure regions. ► We use microseismic monitoring technique to assess rock slope stability. ► Tempo-spatial distribution and characteristics of microseismicity are analyzed. ► Microseismicity shows strong correlation with pre-existing structures of rock slope.► Results between numerical simulation and microseismic monitoring are similar. ► The hazardous regions of rock slope can be identified and delineated.